2020
DOI: 10.1097/mat.0000000000001019
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Associated with Obesity in Patients Undergoing Left Ventricular Assist Device Implantation: A Systematic Review and Meta-Analysis

Abstract: Current data suggest that obesity does not impact survival, but may predispose patients to a higher rate of adverse events during left ventricular assist device (LVAD) support. We performed a systematic review and meta-analysis to assess the effects of obesity on clinical outcomes in LVAD recipients. We searched Medline, Scopus, Cochrane library, and clinicaltrials.gov from inception to February 2019 for studies comparing outcomes in obese (body mass index [BMI]> or ≥30 kg/m2) and nonobese (BMI< or ≤30 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
3
10
2
Order By: Relevance
“…When evaluating the interactions between obesity and prealbumin in our study, we found that patients had similar average distributions of prealbumin levels regardless of obesity status. Furthermore, our results support the findings of other studies that have noted the tendency of obese LVAD patients to have higher rates of postimplant adverse events 17 …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…When evaluating the interactions between obesity and prealbumin in our study, we found that patients had similar average distributions of prealbumin levels regardless of obesity status. Furthermore, our results support the findings of other studies that have noted the tendency of obese LVAD patients to have higher rates of postimplant adverse events 17 …”
Section: Resultssupporting
confidence: 92%
“…Furthermore, our results support the findings of other studies that have noted the tendency of obese LVAD patients to have higher rates of postimplant adverse events. 17…”
Section: Study Findings and Implicationsmentioning
confidence: 99%
“… 76 Though the severely obese patients in this study had higher rates of complications, no differences were found in 30-day or 1-year survival, even after adjusting for age and clinical risk factors. Considering the findings of the meta-analysis by Khan et al 75 in which there was evidence of an obesity paradox in the short-term following LVAD implantation but not at 2 or 3 years, it would be interesting to see if the severely obese patients in this study would also lose their survival advantage at 2 or 3 years or even demonstrate increased mortality at longer-term follow-up.…”
Section: Left Ventricular Assist Devicementioning
confidence: 89%
“…The HeartWare ADVANCE trial ( n = 382) with 48 patients (13%) classified as severely obese found no difference in survival at 2 year follow-up, but had higher risk of driveline infection and acute renal dysfunction. 74 In a meta-analysis of 15 observational studies ( n = 26,842), Khan et al 75 found that obese patients who received an LVAD had significantly decreased all-cause mortality at both 6 months (RR = 0.79, p < 0.001) and one year (RR = 0.87, p = 0.008) compared with non-obese patients. However, there was no significant difference in all-cause mortality at 2 or 3 years, and obese patients had significantly higher risk of device-related infections, pump thrombosis and right sided HF compared to the non-obese.…”
Section: Left Ventricular Assist Devicementioning
confidence: 99%
“…So weight reduction should lead to less morbidity. There is no difference in terms of mortality between obese and non obese patients on LVAD (2,(16)(17)(18). There is still little experience with LSG in this specific patient population.…”
Section: Methodsmentioning
confidence: 99%